Boeica arunachalensis (Gesneriaceae), a New Species from Indian Eastern Himalaya and Typification of five names in Boeica - Borah, Dipankar; Singh, Rajeev Kumar; Taram, Momang; Das, A. P. (Indian Forester, 2020)
No Abstract.